Analysis of Siemens’ Business Model Using SWOT - Ma, Jingyue (Simen Owen Academic Proceedings Series, 2026)
This paper takes Siemens AG as the research object to explore its business model, development challenges and corresponding risk management strategies. With the widespread presence of Siemens household appliances in daily life as the entry point, the study first sorts out the theoretical basis of business models, including their definition, core objectives, significance and four key elements. It then applies SWOT analysis to examine Apple Inc. ’s business model and risk management practices as a reference, and subsequently conducts an in-depth analysis of Siemens’ business model, covering its diversified business layout in energy, infrastructure, healthcare and other fields, digital transformation practices such as the Xcelerator platform, and customer-oriented service strategies. The paper identifies the main risks faced by Siemens, including technological, market, financial and legal risks, and summarizes the company’s targeted risk management measures. Finally, the study concludes with key findings on Siemens’ sustainable growth-driven strategies, notes research limitations related to time constraints and data timeliness, and proposes future research directions regarding adaptive adjustments to its business model amid technological and market changes.